A technical efficiency analysis of intra-central bank settlement mechanism in Eurozone. Issue 31 (3rd July 2022) - Apergis, Emmanuel; Apergis, Iraklis; Apergis, Nicholas
ABSTRACT: This work employs the stochastic frontier method to explore the efficiency of the TARGET2 (T2) balances mechanism across the Eurozone countries. An index is introduced to support the estimation strategy and derives meaningful results from better capturing the mechanism's efficiency. The analysis spans the period 2005–2017 and documents the significant role or inefficiencies influencing the role of T2 from unemployment and labor costs. The absence of T2 would have endangered the viability of the Eurozone to promote trade. There is enormous country heterogeneity on efficiency and inefficiency of the error terms in our model, which indicate persistent structural issues and temporary issues; to ensure its uninterrupted operation, the enhancement of the export orientation of the manufacturing base of countries with the least efficiency (high unemployment and labor costs) is essential.